Islamic Education Values in Marriage Mandailing Indigenous People - Haidir, Haidir; Hizbullah, Muhammad (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to analyze the values of Islamic education in the marriage of the Mandailing community. The main focus of this study is to understand the values of Islamic Education instilled in the marriage of the Mandailing community. This has a vital role as a medium for preserving cultural values for the community while maintaining the values of Islamic Education. A qualitative approach with an ethnographic type is used in this research method, which allows for an in-depth exploration of cultural practices in the marriage of the Mandailing community. Data in this study were collected through observation and interviews with traditional, religious and community leaders of the Mandailing community. The data analysis stage had three main steps: data reduction, data presentation, verification, and conclusion. To ensure the validity of the data, this study applied several validation techniques, such as triangulation of sources and methods, member checks and long-term involvement. Based on the results of the study, it was found that in the marriage of the Mandailing community, ceremonies had been carried out as an effort to preserve the local culture of the community through three events: Event activities before the wedding (pre-wedding), during the wedding (marriage contract), and after the wedding (post-wedding). Pre-wedding has been identified through customary activities before the wedding, namely the custom of marpokkat (makkatai) called family deliberation and welcoming the bride and groom who try to instill moral education values. During the wedding procession (marriage contract), the ijab kabul is guided by the KUA and Penghulu, who instil the values of faith, sharia, and moral education. While in the custom after the wedding, the reception of the groom (who is ready with his traditional clothes), malehan mangan, markobar (man baen hata), and returning to the bride's house has instilled the values of faith, sharia and moral education. This finding provides a new contribution to understanding how Islamic values (faith, sharia, and morals) are internalized through local cultural practices typical of the Mandailing community.